Recruitment Capabilities and Attractive Compensation in Supporting of the Employee Retention Paradigm - Dipa Teruna; Tedy Ardiansyah (Majalah Ilmiah Bijak, 2022)
Generally, employees who have high skills always accept offers from other companies or what we call "high caliber" or "potential" employees. These employees often go in and out of the company, which causes problems for every company. The purpose of this research is to determine the relationship between recruitment, compensation, and employee retention and to determine the most dominant indicators of the three variables mentioned above. The research uses a qualitative approach with a phenomenological approach. The sample is taken from 3 informants, where the average status is as a company leader. nvivo as a tool in analyzing the paradigm or employee retention model. There are four analyses carried out where, in the cluster analysis, it is found that there is a moderate relationship between recruitment, compensation, and employee retention. On the recruitment map for recruitment analysis, the most dominant indicators are competency-based recruitment and online recruitment. For compensation analysis, the most dominant indicators are salary and bonus. The last analysis map for employee retention shows the most dominant career path. It is these dominant indicators that are expected to help with the problem of employee retention in the company.